Karakterisasi Pantulan Akustik Karang Menggunakan Echosounder Single Beam - Baigo Hamuna; Sri Pujiyati; Totok Hestirianoto (JURNAL INTEGRASI, 2014)
The single beam echosounder CruzPro PcFF80 with 200 kHz of frequencies was used for recordings of coral acoustic backscattering. The objectives of this research are to analyze the backscattered signals and to determine the strength and characteristics of coral acoustic backscatters. Data collection was conducted in April 2013 which located in the Seribu Island waters. Acoustics data recording was carried out in Seribu Islands, using single beam echosounder (SBES) CruzPro PcFF80 with operating at 200 and 50 kHz frequencies. An underwater camera was used to validate the acoustic recordings data. The results show that average value of surface backscattering strength (SS) several type of coral at 200 kHz frequency varied between -17.99 dB up -14.65 dB, whereas at 50 kHz frequency varied between -13.33 dB up -9.22 dB. The use of different frequencies will greatly affect the high and low levels of absorption, so that affecting to acoustic backscatter strength.